2022
DOI: 10.2147/ndt.s368123
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sulfonylurea Receptor-1 Levels After Acute Supratentorial Intracerebral Hemorrhage: Implication for Prognosis

Abstract: Objective Sulfonylurea receptor-1 (SUR1) is implicated in acute brain injury. This study was designed to determine relationship between serum SUR1 levels and severity, early neurologic deterioration (END) plus clinical outcome after intracerebral hemorrhage (ICH). Methods Serum SUR1 levels of 131 ICH patients and 131 healthy controls were quantified in this prospective, observational study. END was defined as an increase of 4 or more points in the National Institutes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several clinical studies suggest that serum SUR1 and TRPM4 concentrations change with disease progression after CNS injury because of disruption of the BBB, suggesting that serum SUR1 and serum TRPM4 levels may have the potential to be new markers of CNS injury to reflect disease progression ( Jha et al, 2017 ; Dundar et al, 2020 ; Zhuge et al, 2022 ). In this study, we found that the serum SUR1 and TRPM4 concentrations showed a single peak change in the acute phase in rats after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies suggest that serum SUR1 and TRPM4 concentrations change with disease progression after CNS injury because of disruption of the BBB, suggesting that serum SUR1 and serum TRPM4 levels may have the potential to be new markers of CNS injury to reflect disease progression ( Jha et al, 2017 ; Dundar et al, 2020 ; Zhuge et al, 2022 ). In this study, we found that the serum SUR1 and TRPM4 concentrations showed a single peak change in the acute phase in rats after TBI.…”
Section: Discussionmentioning
confidence: 99%